The Use of Environmental Approach in the Work with Children with ASD - M.V. Yaremchuk (Moscow State University of Psychology and Education, 2019)
The insufficient development of adaptive strategies often hinders the reduction of stress, worsens the condition of the child and the family. Therefore, it is important to create special conditions for children that contribute to the gradual development of new situations, especially for children with autism spectrum disorders that have adaptation difficulties due to their developmental features. Professionals of the Center for Curative Pedagogy in Moscow build their work based on an environmental approach, which implies the formation of individual conditions for each child, aimed at mastering more and more new situations offered to the child and family by society. The article reveals the concept of the environment as a set of relations of a child with its surrounding reality: object and social. The types of environment are distinguished: comfortable, developing, stressful. The importance of creating a developmental environment for the full disclosure of the potential of the child is emphasized. Characteristics of various environments are given: spatio-temporal, emotional, semantic, which are individually selected for sessions with a child, depending on the tasks assigned to the work. The examples illustrating the work in line with the environmental approach are considered.